Interferons Alpha, Beta, and Omega - Meager, Anthony (Cytokines, 1998)
Interferon alpha (IFN-α) is a mixture of closely related proteins, termed “subtypes,” expressed from distinct chromosomal genes. Interferon β (IFN-β) is a single protein species and is molecularly related to IFN-α subtypes, although it is antigenically distinct from them. IFN omega (IFN-ω) is antigenically distinct from IFN-α and IFN-β but is molecularly related to both. The genes of three IFN subtypes are tandemly arranged on the short arm of chromosome 9. They are transiently expressed following induction by various exogenous stimuli, including viruses. They are synthesized from their respective mRNAs for relatively short periods following gene activation and are secreted to act, via specific cell surface receptors, on other cells. IFN-α subtypes are secreted proteins and as such are transcribed from mRNAs as precursor proteins, pre-IFN-α, containing N-terminal signal polypeptides of 23 hydrophobic amino acids (aa) mainly. Pre-IFN-β contains 187 aa, of which 21 comprise the N-terminal signal polypeptide and 166 comprise the mature IFN-β protein. IFN-ω contains 195 aa—the N-terminal 23 comprising the signal sequence and the remaining 172, the mature IFN-ω protein. At the C-terminus, the aa sequence of IFN-ω is six residues longer than that of IFN-α or IFN-β proteins. IFN-α, as a mixture of subtypes, and IFN-ω may be produced together following viral infection of null lymphocytes or monocytes/macrophages. The biological activities of IFNs are mostly dependent upon protein synthesis with selective subsets of proteins mediating individual activities. IFNs can also stimulate indirect antiviral and antitumor mechanisms, depending upon cellular differentiation and the induction of cytotoxic activity.